The Potential of Serverless Edge-powered Islands for Web Development - Vepsäläinen, Juho; Vuorimaa, Petri; Hellas, Arto (Journal of Web Engineering, 2025)
Web developers face two significant challenges when developing their applications and websites: latency and payload size. Given that web services rely on servers, the related communication incurs a cost in terms of latency. In contrast, the payload passed to the client incurs a communication cost, not to mention the computational cost to the client. The concept of serverless edge computing, built on top of content delivery networks (CDNs), is an approach that has begun to gain the attention of web developers for its promise of lower latencies due to its efficiencies in communication thanks to globally distributed networks and replication. Islands architecture is a technical approach that addresses payload size by giving developers easy ways to defer and potentially even avoid the cost of loading content. Combined, these two approaches form edge-powered islands and, in this article, we examine how the combination can help to address these two notable costs web developers have to consider in their daily work. Our findings indicate that edge-powered islands can provide a way to introduce interactivity to otherwise static websites while wrapping dynamic portions of a page within islands to gain the benefits of static approaches in more dynamic contexts, such as storefronts. In addition, islands can provide loading benefits even for more application-like websites, such as social networks, and give web developers an additional control layer in their development work.